A Narrative Tour of Transformative Learning in Doctoral Students - Kalpana Gupta; Kristi Archuleta Frush; Qi Sun (Adult Education Research Conference, 2013)
This roundtable emphasizes the literature on transformative learning as well as a phenomenological investigation through narratives. Storytelling through lived experiences provides first hand details into the process of finding oneself. The findings through this type of exchange can reveal new insight to the practice of teaching and learning.